The new rules of running : five steps to run faster and longer for life - Vad, Vijay; Allen, Dave, 1968- (Avery, a member of Penguin Group (USA), 2014)
"The definitive guide to injury-free running, racing, and marathoning, from top sports medicine specialist Vijay Vad, The New Rules of Running illustrates proper technique, shows step-by-step exercises, and explains how to prevent and treat the most common running injuries to keep you running healthily and happily for life"--